The Comprehensive Midwifery Care For Mrs “D” With Prenatal Yoga To Reduce Back Pain In Third Trimester Of Pregnant Women - Ra. Aminah Maya; Sukmawati (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Backgrounds: Back pain can have an impact on the mother's posture so that it can cause the mother's posture to change into lordosis and kyphosis. One of the holistic treatments that can reduce back pain is prenatal yoga. Purpose: To provide comprehensive midwifery care to Mrs.